Uji Coba Media Banner Pencegahan Anemia Pada Remaja Putri - Ummah, Fadhilah Hamiatul; Majid, Ruslan; Bahar, Hartati (Jurnal Pengabdian Masyarakat (JUDIMAS), 2025)
Anemia is a disease that occurs when the body lacks healthy red blood cells or when red blood cells do not function properly. This causes the body's organs to not get enough oxygen, causing anemia sufferers to have pale skin and get tired easily. The risk of suffering from anemia in adolescent girls is higher, this is because adolescent girls experience puberty in the form of menstruation. The aim of this service is to determine the effectiveness of nutrition education using cheerful banner media (preventing adolescent anemia) on knowledge and attitudes in efforts to prevent anemia in adolescent girls at SMK Negeri 3 Kendari in 2024. This service method uses quantitative with a Pre-Experimental approach, the design form used is a control group that is not equivalent to the pre-test and post-test. The sample for this service amounted to 69 people using a simple random sampling technique. The results of the service show that there is an influence of cheerful banner media on knowledge and attitudes with a p-value from the Wilcoxon test for knowledge, namely 0.000, and an attitude p-value of 0.000 or <0.05. It can be concluded that there is an influence of the use of banner media on knowledge and attitudes in efforts to prevent anemia among young women at SMK Negeri 3 Kendari in 2024. Reducing the teaching staff is expected to increase the role in providing education to young women about health, especially regarding preventing anemia, by using health promotion media such as banners or other health promotion media so that information communication can be more interesting and easy to understand